Inovasi Pengelolaan Sampah Berbasis Partisipasi: Transformasi Limbah Menjadi Kompos, Lilin Aromaterapi, dan Ecobrick di Desa Gembyang - Mutaqin, Enjen Zaenal (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
Environmental issues related to both organic and inorganic waste have become a serious challenge in Pemalang, including in Gembyang Village. Poorly managed waste has the potential to cause environmental damage. This community service activity focuses on education through innovative workshops aimed at equipping local residents with skills to process waste into valuable products such as compost, aromatherapy candles, and ecobricks. The method used in this workshop is a participatory approach, where the community actively engages in the training and waste processing activities. The workshop not only addresses environmental aspects but also introduces the economic potential of waste processing. The results show an increase in the community's knowledge and awareness regarding the importance of sustainable waste management. Additionally, the products created have economic value that can be further developed. In conclusion, this workshop successfully provides a concrete solution for waste management while simultaneously creating new economic opportunities for the residents of Gembyang Village.